Proyecto de factibilidad para la creación de una empresa de servicios académicos de tareas dirigidas y nivelación on-line para niños de nivel de educación básica de acuerdo al pensum de estudios del Ministerio de Educación y Cultura, en el D.M. de Quito - Molina Carrión, Wilma Beatríz (2016)
In this research, a systematic administrative study was conducted with the aim of making a "PROJECT FEASIBILITY FOR THE CREATION OF A COMPANY OF CHILDREN LEVEL BASIC EDUCATION ACADEMIC TASKS ADDRESSED AND GRADING ON-LINE AGREEMENT. PENSUM TO STUDY THE MINISTRY OF EDUCATION AND CULTURE IN QUITO DM "for the development of this research I used methods and techniques that allowed me to collect the necessary information and data; the methods used were Deductive; Inductive; Descriptive. The techniques applied were direct observation; Surveys a total of 400 applied to the sample D.M. families of Quito and 10 companies that are in direct competition with "SMART CHILDREN ON-LINE". Market research in the demand and supply existing unmet demand also determined, as well as; Per capita consumption with an average annual consumption of 108 times per family. relation to the Service, Price, Place, Promotion and Advertising to be used by the company was established. Within the Technical Study in relation to the size determined aspects such as capacity installed and used; so much so that based on the capacity utilization of 90%, and by an efficient and effective for providing the service process, the company "SMART CHILDREN ON-LINE" will address a number of seven teachers, a total of 9,100 children spending on average 3 to 4 hours in their first year of life. In the location of the project I set the macro and micro location will be in will be located in Canton Rumiñahui, Parish Sangolquí, Cashapamba Sector in the streets Av Antonio Tandazo and Quinabanda, evaluating by favorable location factors.; in engineering project detailing what the operational process, the phases of the service itself and the distribution of office. In the Administrative study raised the establishment of the company as a limited liability company under the name SMARTH CHILDREN ON-LINE "," formed by two partners; and in terms of organizational structure it is defined by organizational charts and manuals functions. The financial study indicates that for creating the company an investment of $ $$ 140,871.54 specifying fixed assets, deferred and necessary working capital, which will be financed with equity $ 25,000 and the $ 114,250 is required through a loan with Banco de Guayaquil. Financial Evaluation in the respective indicators show a profitable and sustainable project, based on an NPV of $ 239,395.28, an TIR of 35.26%; one RBC of $ 2.19 and the recovery time will be 1 year 25 days from the launch of the project; Sensitivity Analysis allowed us to determine that the project does not support an increase in costs of 14.98% and a decrease in revenues of 12.10%, therefore suffers no sensitivity to changes to that margin in the two variables analyzed. Regarding the conclusions indicate the need for the creation of the company, in order to provide the Service Equalization and Tasks Addressed On-Line, because there is acceptance of the creation of the company and the manifestation of that would use from service. Recommendations entrench and support the conclusions of what should be done for the creation and implementation of the company "SMART CHILDREN ON-LINE" since there is the necessary demand is economically profitable and also would generate jobs.